Alkaloids Isolated from Natural Herbs as the Anticancer Agents. (4th September 2012) - Lu, Jin-Jian; Bao, Jiao-Lin; Chen, Xiu-Ping; Huang, Min; Wang, Yi-Tao
Abstract : Alkaloids are important chemical compounds that serve as a rich reservoir for drug discovery. Several alkaloids isolated from natural herbs exhibit antiproliferation and antimetastasis effects on various types of cancers both in vitro and in vivo . Alkaloids, such as camptothecin and vinblastine, have already been successfully developed into anticancer drugs. This paper focuses on the naturally derived alkaloids with prospective anticancer properties, such as berberine, evodiamine, matrine, piperine, sanguinarine, and tetrandrine, and summarizes the mechanisms of action of these compounds. Based on the information in the literature that is summarized in this paper, the use of alkaloids as anticancer agents is very promising, but more research and clinical trials are necessary before final recommendations on specific alkaloids can be made.